Вплив цукровмісної сировини на якість шампанських виноматеріалів - Гречко, Ніна Яківна; Бабич, Ірина Михайлівна; Пилипенко, Олексій Юрійович; Ільїн, Ілля Сергійович (My University, 2015)
Було проведено дослідження впливу використання складу лікерів, виготовлених на основі сахарози та цукру-піску, на якість ігристих вин. Досліджувався сухий білий виноматеріал, з шампанського сорту винограду Шардоне. У роботі досліджено динаміку зміни основних фізико-хімічних показників в процесі вторинного бродіння з використанням виноматеріалу, сахарози та цукру-піску, на якість готового ігристого вина. Під час шампанізації були використані активовані сухі дріжджі наступних штамів: EC 1118, CH 420, LS2, LW 317-30. In the thesis was research of the influence of liquor prepared from sucrose and sugar, for quality sparkling wines. Research dry white wine, made from champagne grapes Aliquot and Chardonnay, samples of sucrose and sugar. In this paper, followed the basic dynamics of physical and chemical characteristics during secondary fermentation using wine, sucrose and sugar, the quality of the finished sparkling wine. While champagne were used, including active dry yeast «Lalvin», issued jointly by the Institute Lallemand and Oenology in Champagne. Secondary fermentation in the bottle carried by 0.33 dm3, in order to research the biochemical changes and identify all the organoleptic and physico-chemical parameters of samples from sucrose and sugar. The process of fermentation lasted for 20 days at t = 14-16Со. After every 3 days fermentation, all samples were analyzed for physico-chemicalperformance.
Keywords: кафедра теплоенергетики та холодильної техніки; кафедра біотехнології продуктів бродіння і виноробства; вино ігристе; Шардоне; sparkling wine